Synergistic Effect of Some Natural Substances in Combination with Antibiotics on MDR Klebsiella isolates (Medico Legal Update, 2020)
This study included the collection of 210 samples of Mid-stream urine samples of the patients who wereconfirmed to be infected with UTI by conducting a general urine examination and the patients of ALAmriya General Hospital, Ramadi Teaching Hospital and Fallujah Teaching Hospital for the period between2017 and January 2018.  The results of the diagnosis showed a seven isolations of 17.5% of the total of40 bacterial isolates. These isolations were diagnosed in aerobic conditions according to the microscopicexamination and Culture characteristics on blood agar base and MacConkey agar as well as the biochemicaltests, Diagnosis was confirmed using the modern diagnostic system VITEK2.The synergistic activity of the natural substances used (sesame oil, olive oil, and royal Jelly) was studiedagainst Klebsiella isolates by interfering with some of the antibiotics by disk diffusion method (Gentamicin,Amikacin, Ceftriaxone, Trimethoprim-Sulfamethoxazol, Nitrofurantoin, Amoxicillin/Clavulanic acid,Ciprofloxacin), and the synergic efficacy of natural materials was studied by adding 10 ul of sterilepasteurized natural substance directly to the antibiotic disk separately. The results showed increased efficacyof some antibiotics, especially Ciprofloxacin, Ceftriaxone and Amoxicillin/Clavulanic acid. so it can beconcluded that sesame oil and royal Jelly have synergistic effectiveness in increasing the effectiveness ofsome antibiotics against Klebsiella.